INTERSEPSI HUJAN DAN PENGARUHNYA TERHADAP PEMINDAHAN ENERGI DAN MASSA PADA HUTAN TROPIKA BASAH ” STUDI KASUS TAMAN NASIONAL LORE LINDU” - Abdul Rauf; H. Pawitan; T. June; C. Kusmana; G. Gravenhorst (Universitas Tadulako, 2008)
The field observation of this research was conducted from June 2005 – May 2007 in tropical rainforest at Lore Lindu National Park Central Sulawesi. The main objectives of this research were to study (i) the relationships between interception loss and rainfall properties and vegetation characters and to determine the dominant factors affected (ii) the effect of rainfall interception on energy flux and mass transfer and (iii) the dynamics of vertical energy flux under the forest and grass land. Rainfall interception was 36.34 % of gross rainfall in 200 events, Depth rainfall and LAI factors had strong effects on rainfall interception. The relationships could be expressed as Ic = 0.980+0.239P+0.035LAI (R2 = 0.78). The output of this equation was compared with Gash model and the observation value showed that deviation of the equation was 1 % and less than Gash model, so that equation gave as good result as Gash model gave. By considering the data requirements and calculation procedures it was concluded that this equation is applicable for interception prediction. Land use type had effects on radiative and energy balance. Net radiation (Rn) in the forest was 10.66 MJ/m2/day and higher than in the grass land where incident global radiation was similar. Vertical latent heat flux in the forest was 9.53 MJ/m2/day or 89.40% Rn in rainy day and 8.41 MJ/m2/day or 74.56 % Rn in dry day, on the other hand, in the grass land, sensible heat flux was higher than latent heat flux of all weather condition. Direct effect of rainfall interception on energy flux and mass transfer might be described that is needed latent heat 9.0 MJ/m2/rainy day to evaporate the rain intercepted of 3.69 mm/rainy day. Effect of rainfall interception had positive correlation with latent heat flux and the negative correlation with sensible heat flux.